Cost-effectiveness of balloon kyphoplasty in patients with symptomatic vertebral compression fractures in a UK setting. - Ström, O; Leonard, C; Marsh, D; Cooper, C (2010)
SUMMARY: Balloon kyphoplasty (BKP) is a procedure used to treat vertebral compression fractures (VCFs). We developed a cost-effectiveness model to evaluate BKP in United Kingsdom patients with hospitalised VCFs and estimated the cost-effectiveness of BKP compared to non-surgical management. The results indicate that BKP provides a cost-effective alternative for treating these patients. INTRODUCTION: VCFs of osteoporotic patients are associated with chronic pain, a reduction in health-related quality of life (QoL) and high healthcare costs. BKP is a minimally invasive procedure that has resulted in pain relief, vertebral body height-restoration, decreased kyphosis and improved physical functioning in patients with symptomatic VCFs. BKP was shown to improve health-related QoL in a 12-month interim analysis of a randomised phase-III trial. METHODS: The objectives of this study were to develop a Markov cost-effectiveness model to evaluate BKP in patients with painful hospitalised VCFs and to estimate the cost-effectiveness of BKP compared with non-surgical management in a UK setting. It was assumed that QoL-benefits found at 12 months linearly approached zero during another 2 years, and that patients receiving BKP warranted six fewer hospital bed days compared with patients given non-surgical management. RESULTS: The procedure was associated with quality-adjusted life-years (QALY)-gains of 0.17 and cost/QALY-gains at 8,800 pound sterling. The results were sensitive to assumptions about avoided length of hospital-stay and persistence of kyphoplasty-related QoL-benefits. CONCLUSION: In conclusion, the results indicate that BKP provides a cost-effective alternative for treating patients with hospitalised VCFs in a UK-setting.